Early detection of cardiotoxicity in children receiving adriamycin: A comparison of tissue Doppler and standard echocardiography with Troponin I as an early marker. - Mina Farshidgohar; Majid Vafaie; Sonia Oveisi; Maryam Bakhshi (PLoS ONE)
Background Adriamycin (doxorubicin hydrochloride) is a widely used chemotherapeutic agent for treating various malignancies. However, its most significant adverse effect is cardiac toxicity. Early detection of Adriamycin-induced cardiac dysfunction is crucial in preventing heart failure through interventions such as angiotensin-converting enzyme inhibitors and beta-blockers. Adriamycin-induced cardiotoxicity is classified into Type I (irreversible, involving cardiomyocyte necrosis) and Type II (potentially reversible, involving cardiomyocyte dysfunction). Type I toxicity is more common, leading to long-term heart cell necrosis. Monitoring cardiac function in children receiving Adriamycin is essential. Non-invasive imaging techniques like transthoracic echocardiography, cardiac magnetic resonance imaging, and computed tomography are used to evaluate left ventricular (LV) systolic and diastolic functions. However, the role of cardiac Troponin I for early detection of anthracycline-induced cardiomyopathy remains debated. Methods This prospective study included 50 children (26 males, 24 females) with a median age of 8 years (range: 2-14) receiving Adriamycin. Troponin I levels were measured before and 24 hours after Adriamycin administration. Standard Doppler Echocardiography and Tissue Doppler Imaging (TDI) were performed at baseline, one month, and six months' post-treatment to assess LV function. Results Out of 50 patients, two showed a decrease in left ventricular ejection fraction (LVEF) below the normal range (<55%) one month post-treatment, along with significant increases in Troponin I levels. No significant decline in LVEF was observed at one or six months' post-treatment using Standard Doppler Echocardiography. However, TDI revealed a decrease in LV systolic and diastolic function in all patients one month after Adriamycin administration. Conclusion TDI is more sensitive than Standard Doppler Echocardiography in detecting Adriamycin-induced cardiotoxicity. Elevated cardiac Troponin I levels correlate with a decline in LVEF, but subclinical cardiac dysfunction is better detected with TDI.